2007
DOI: 10.1097/01.ccm.0000254341.87098.a4
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 blocks in vitro cardiac myocyte depression induced by tumor necrosis factor-α, interleukin-1β, and human septic shock serum

Abstract: These data demonstrate that depression of in vitro cardiac myocyte contraction induced by proinflammatory cytokines and septic serum can be blocked by TGF-beta1. TGF-beta1 may have potential as therapy for sepsis-associated myocardial depression in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 42 publications
0
28
1
3
Order By: Relevance
“…Even though a role of either TNF-a or IL-6 as suggested by animal and some human studies in the well known and reversible myocardial depression of septic shock (Vincent et al, 1992;, Cain et al, 1999;Pathan et al, 2004;Janssen et al, 2005;Hoesel et al, 2007;Joulin et al, 2007;Kumar et al, 2007; could not be established, our observations suggest that effects on the heart may have been offset in part by concomitant complement activation. Together with decreased bacterial clearance and survival of septic mice with C3 deficiency , the current data suggest that the association of complement activation and mortality reported for human sepsis Selberg et al, 2000;Groeneveld et al, 2003) is not caused by adverse hemodynamic effects.…”
Section: Inflammatory Mediators and Hemodynamics In Human Septic Shoccontrasting
confidence: 64%
See 1 more Smart Citation
“…Even though a role of either TNF-a or IL-6 as suggested by animal and some human studies in the well known and reversible myocardial depression of septic shock (Vincent et al, 1992;, Cain et al, 1999;Pathan et al, 2004;Janssen et al, 2005;Hoesel et al, 2007;Joulin et al, 2007;Kumar et al, 2007; could not be established, our observations suggest that effects on the heart may have been offset in part by concomitant complement activation. Together with decreased bacterial clearance and survival of septic mice with C3 deficiency , the current data suggest that the association of complement activation and mortality reported for human sepsis Selberg et al, 2000;Groeneveld et al, 2003) is not caused by adverse hemodynamic effects.…”
Section: Inflammatory Mediators and Hemodynamics In Human Septic Shoccontrasting
confidence: 64%
“…Although myocardial depression may be associated with cardiomyocyte signaling by release of interleukin (IL)-1, IL-6 or tumor necrosis factor alpha (TNF-a) and NO in experiments (Vincent et al, 1992;Cain et al, 1999;Groeneveld et al, 2003;Janssen et al, 2005;Kumar et al, 2007, Joulin et al, 2007, Hoesel et al, 2007, only IL-6 may be involved in vivo in the myocardial depression of (meningococcal) septic shock in humans (Pathan et al, 2004). Moreover, the factors in septic shock serum mainly responsible for myocardial depression in vitro vary between studies (Joulin et al, 2007;Kumar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, TNF alpha and IL1 [18] have also a depressive effect on single cell function. Conversely, TNF beta may prevent contractile dysfunction induced by IL1 [18], and an enhanced sensitivity to IGF1 induced an increase in cell contraction [10]. Skeletal myoblasts induced a delay in repolarisation of cardiomyocytes in coculture.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, in vitro experiments also have shown that cytokine CXCR12 induces deleterious effects on cardiomyocytes contractility [26]. Similarly, TNF alpha and IL1 [18] have also a depressive effect on single cell function. Conversely, TNF beta may prevent contractile dysfunction induced by IL1 [18], and an enhanced sensitivity to IGF1 induced an increase in cell contraction [10].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation